2018
DOI: 10.1080/00934690.2018.1479085
|View full text |Cite
|
Sign up to set email alerts
|

Iron Smelting in Sudan: Experimental Archaeology at The Royal City of Meroe

Abstract: The Royal City of Meroe, ca. 200 km north of Khartoum in the modern-day Republic of the Sudan, was an ancient capital of the Kingdom of Kush. From the 3rd century B.C. to the 4th century A.D., Kushite rulers controlled significant territory from the banks of the Nile at Meroe, in part through their ability to ensure the production of significant quantities of iron. The extensive archaeological remains of Meroitic iron production have been investigated over decades, and recently a series of experimental iron sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…The values of furnace efficiency used in our model are in accordance with values reported from experiments [ 5 , 131 , 136 , 158 – 160 ] and other studies on the resource consumption of pre-industrial metallurgy outside the Italian peninsula ( Table 5 ). In smelting experiments conducted on Elba Island, Benvenuti et al [ 19 ] obtained a furnace inefficiency of 2.5 kg/kg and Brambilla [ 161 ] a furnace inefficiency of 6.17 kg/kg.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The values of furnace efficiency used in our model are in accordance with values reported from experiments [ 5 , 131 , 136 , 158 – 160 ] and other studies on the resource consumption of pre-industrial metallurgy outside the Italian peninsula ( Table 5 ). In smelting experiments conducted on Elba Island, Benvenuti et al [ 19 ] obtained a furnace inefficiency of 2.5 kg/kg and Brambilla [ 161 ] a furnace inefficiency of 6.17 kg/kg.…”
Section: Discussionsupporting
confidence: 86%
“…Furnace design contributed to the efficiency of smelting; smelting in shaft furnaces might have consumed less charcoal than smelting in a pit furnace [ 4 , 134 ]. Also the furnace diameter [ 135 ] as well as slag tapping [ 136 ] and air supply [ 135 , 137 ] might have influenced efficiency. However, skill of the smelters [ 136 ], ore mineralogy [ 4 , 136 ], charcoal quality and the iron economy [ 137 ] are also important determinants of the efficiency.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the experimental iron smelting campaigns that form a major research avenue of the current archaeometallurgical investigations (Charlton and Humphris 2017;Humphris et al 2018b), a mining location was identified in the hills approximately 9 km to the east of Meroe. During intensive systematic survey of the mining landscape, a number of slag fragments were recovered, within one of which was a charcoal sample.…”
Section: Late and Post-meroitic Periods Hamadabmentioning
confidence: 99%
“…The quantity of charcoal used during iron production in the Meroe region is as yet unknown and likely changed over time in relation to changing intensity of production and technological style. Recent experimental work (Charlton and Humphris 2017;Humphris et al 2018b) suggests that between 30 and 90 kg of charcoal could have potentially been required for a single smelt, with additional charcoal needed for ore roasting and smithing. Further experiments are being conducted to test such aspects of the technology as fuel requirements.…”
Section: How Much Charcoal?mentioning
confidence: 99%